Negative magnetisation and magnetic exchange interactions in Fe3+ substituted Ca2NdCr2NbO9. Issue 9 (1st May 2022) - Meng, B.; Fu, Q.S.; Li, C.L.; Chen, X.H.; Qiu, Y.; Yuan, S.L.
Abstract: The crystal structure, magnetic properties, and magnetic exchange interactions of Fe 3+ -substituted Ca2 NdCr2- x Fe x NbO9 single-phase perovskites were systematically studied in. The substituted ranges of 0 ≤ x ≤ 0.6 using a standard solid-state reaction. X-ray diffraction results indicated an orthorhombic structure for all the samples. Tunable negative magnetisation phenomena were observed for samples corresponding to x = 0.25 to x = 0.5 and the maximum compensation temperature was observed in the x = 0.3 sample. Detailed magnetic measurements demonstrated the coexistence of the normal and inverse magnetic moments. Furthermore, the complicated magnetic exchange interactions were described using the fitting model obtained in the low-temperature region of the field cooling curves. The magnetic switching effect and magnetocaloric effect were investigated based on fundamental physics and potential applications.